2015
DOI: 10.1111/ejh.12519
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of ultrasound‐detected asymptomatic long‐term central vein catheter‐related thrombosis and fibrin sheath in cancer patients

Abstract: Asymptomatic DVT and fibrin sheaths do not represent per se an indication for removal of functioning CVC in cancer patients who need central vein access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 25 publications
(51 reference statements)
1
33
0
1
Order By: Relevance
“…Medical therapy is effective only in the early days after catheter implantation . In cases of calcified fibrin sheath, which represent 45% of residual fibrin sheaths, anticoagulation therapy seems to be useless . Resection under cardiopulmonary bypass has previously been described in cases of infected fibrin sheath embolization in the right atrium and when medical therapy has failed …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Medical therapy is effective only in the early days after catheter implantation . In cases of calcified fibrin sheath, which represent 45% of residual fibrin sheaths, anticoagulation therapy seems to be useless . Resection under cardiopulmonary bypass has previously been described in cases of infected fibrin sheath embolization in the right atrium and when medical therapy has failed …”
Section: Discussionmentioning
confidence: 99%
“…In case of medical therapy failure, close follow‐up is especially needed. Risk factors for fibrin sheath emergence have been previously studied . Small vein area and low platelet count seem to be associated with higher fibrin sheath prevalence .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even if mechanisms of fibroblastic sleeve and thrombosis formation are well-known, their relationship remains still unclear. 21 16 US guidance is nowadays considered a standard of care for catheter insertion and appropriate vein choice. 22 Since 2008, an extensive body of evidence has demonstrated that real-time ultrasound-guided venipuncture reduces the risk of CRT.…”
Section: Thrombosis and Fibroblastic Sleevementioning
confidence: 99%